2017
DOI: 10.1002/med.21455
|View full text |Cite
|
Sign up to set email alerts
|

Glypican‐3: A promising biomarker for hepatocellular carcinoma diagnosis and treatment

Abstract: Liver cancer is the second leading cause of cancer-related deaths, and hepatocellular carcinoma (HCC) is the most common type. Therefore, molecular targets are urgently required for the early detection of HCC and the development of novel therapeutic approaches. Glypican-3 (GPC3), an oncofetal proteoglycan anchored to the cell membrane, is normally detected in the fetal liver but not in the healthy adult liver. However, in HCC patients, GPC3 is overexpressed at both the gene and protein levels, and its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(216 citation statements)
references
References 171 publications
(378 reference statements)
4
208
2
2
Order By: Relevance
“…For example, HCC cell has asialoglycoprotein (ASGP) receptor where ligands from nanocarrier like galactoside, galactosamine, lactose, sterylglucoside, pullulan, lactobionic acid complementarily bind to ASGP receptor. 95 Bioactive moieties such as chemotherapeutic drug or specific gene will be released into the liver cancer specific site after the nanocarriers bind to the surface. Figure 7 shows the active targeting strategies of nanocarrier for liver.…”
Section: Strategies For Active Targeting To Livermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HCC cell has asialoglycoprotein (ASGP) receptor where ligands from nanocarrier like galactoside, galactosamine, lactose, sterylglucoside, pullulan, lactobionic acid complementarily bind to ASGP receptor. 95 Bioactive moieties such as chemotherapeutic drug or specific gene will be released into the liver cancer specific site after the nanocarriers bind to the surface. Figure 7 shows the active targeting strategies of nanocarrier for liver.…”
Section: Strategies For Active Targeting To Livermentioning
confidence: 99%
“…Glypican-3A is recently reported as a promising biomarker for hepatocellular carcinoma. 95 In active targeting, scientists developed different gene silencing technologies such as antisense technologies, small activating RNAs (saRNAs) for liver tumor targeting. The development of a saRNAs upregulates the enhancer binding protein α (CEBPA).…”
Section: Strategies For Active Targeting To Livermentioning
confidence: 99%
“…Third, this study focused on only GPC-3-specific T cell responses and thus may not reflect the entirety of the immune surveillance machinery of HCC. Although we reckon that GPC-3 is the best TAA for studies like this one because of its high immunogenicity [12] and for it being the center of attention for the recent advances in HCC immunotherapy and adoptive T-cell therapy [30,29,[38][39][40][41], investigation of other TAAs should be considered in future studies. In summary, our study here demonstrated that HCC-specific T cell responses are readily detectable in patients with liver cirrhosis relative to non-cirrhotic controls.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A*0201-restricted HCC-specific peptides of AFP [137][138][139][140][141][142][143][144][145] (PLFQVPEPV), NY-ESO-1 157-165 (SLLMWITQC), MAGE-A3 112-120 (KVAELVHFL), MAGE-A10 [254][255][256][257][258][259][260][261][262] (GLYDGMEHL), SSX-2 [41][42][43][44][45][46][47][48][49] (KASEKIFYV) and p53 [149][150][151][152][153][154][155][156][157] (STPPPGTRV) at purities ranging from 82.78 to 97.99% were also obtained from ProImmune Ltd. For these HCC-associated epitope-specific peptides, corresponding PE-labeled MHC class I dextramers were obtained from Immudex (Copenhagen, Denmark). Further, HBV-specific 15-mer overlapping peptides covering the core (4 pools from 41 peptides) and polymerase regions (8 pools from 165 peptides) were purchased from ProImmune Ltd. Also, HLA-A*0201-restricted HBV-specific peptides Core [18][19][20][21][22][23][24][25][26][27] (FLPSDFFPSV), Env [183][184][185][186][187][188]<...>…”
Section: Peptides Hla Class I Multimers and Recombinant Proteinsmentioning
confidence: 99%
“…Glypican-3 is an important player in the Wnt, Hedgehog, and YAP signaling cascades involved in cancer cell proliferation and migration (108,109). It is overexpressed in hepatocarcinoma and lung carcinoma and was reported as a poor prognosis marker in hepatocarcinoma.…”
Section: Proteoglycansmentioning
confidence: 99%